Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.23 Example continued

We determine F(x)F(x) using partial fractions. We have

2x2-1=1x-1-1x+1\frac{2}{x^{2}-1}={\frac{1}{x-1}-\frac{1}{x+1}}

so F(x)=log|x-1|-log|x+1|=log|x-1x+1|.F(x)={\log|x-1|-\log|x+1|=}\,{\log\left|\frac{x-1}{x+1}\right|.} Hence eF(x)=|x-1x+1|.e^{F(x)}={\left|\frac{x-1}{x+1}\right|.} In this process we can essentially ignore the absolute value sign (which at worst means multiplying by (-1)(-1)), so we can take for the integrating factor: I(x)=x-1x+1I(x)=\frac{x-1}{x+1}.

Multiplying both sides through by I(x)I(x), we obtain the equation

x-1x+1dydx+2y(x+1)2=1x+1\frac{x-1}{x+1}\frac{dy}{dx}+\frac{2y}{(x+1)^{2}}=\frac{1}{x+1}

where the left-hand side is ddx(x-1x+1y).{\frac{d}{dx}\left(\frac{x-1}{x+1}y\right).}